CELL@CELL HIGHER DIMENSIONAL STRUCTURES - PÎRVAN-MOLDOVAN, Atena; DIUDEA, Mircea V. (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Local domains of n-spaces surrounded by the common Euclidean 3D-space may exist in complex chemical (mineral or synthetic) structures. In this paper, two classes of the simplest clusters embedded in n-dimensional spaces higher than three are designed by operations on maps and their properties discussed.